Nepal Contingency Planning Project - World Bank (Washington, DC, 2013)
The Nepalese authorities have made important progress in strengthening the financial stability framework. This framework consists of provisions for liquidity support to banks, supervisory practices, and problem bank resolution mechanisms. Some liquidity facilities have been put in place, supervisory actions strengthened, and amendments to bank resolution laws have been passed that improved the ability of the Nepalese Government to manage the growing financial sector. Notwithstanding this progress, some additional refinements are warranted. The banking sector is growing rapidly, with new entrants increasing the risk profile of the system. At the same time, the economic conditions of the country are less beneficial than in the past. Accordingly, some strengthening of the existing framework is advisable. Areas for strengthening include: preconditions for effective crisis management; development of a crisis management framework; and preparation of a step-by-step plan for meeting the crisis. This report focuses on two aspects of contingency planning. First, a number of structural reforms are necessary to make the crisis management framework efficient. These preconditions for an effective crisis management framework may take time to implement but should be initiated immediately. If a crisis were to emerge before these reforms are completed, the crisis will be more difficult to contain and resolve. Second, an Action Plan for dealing with the unfolding crisis is proposed. While the specifics will depend on the causes of the crisis and the particular path the crisis takes, principles for addressing the crisis will be discussed.